2014
DOI: 10.1097/brs.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Skeletal Maturity Scoring System

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…This period is best represented by TW3 stage G (dominant capping appearance in the majority of the epiphyses of all 5 digits 2 , 3 ), corresponding to SSMS stage 3 2 and TOCI stage 5. Advanced capping (TW3 stage G) of the thumb proximal phalanx also matched with advanced capping (TW3 stage G) in all 4 ulnar digits, with a concordance rate of 82.0% (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This period is best represented by TW3 stage G (dominant capping appearance in the majority of the epiphyses of all 5 digits 2 , 3 ), corresponding to SSMS stage 3 2 and TOCI stage 5. Advanced capping (TW3 stage G) of the thumb proximal phalanx also matched with advanced capping (TW3 stage G) in all 4 ulnar digits, with a concordance rate of 82.0% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sanders et al proposed the digital skeletal age (DSA) score 1 and then the simplified skeletal maturity system (SSMS) 2 , derived from the original Tanner-Whitehouse III radius, ulna and short bone (RUS)—or TW3—method, and these systems were recognized widely as the gold standards for clinical management of idiopathic scoliosis. In a recent multicenter validation study, the SSMS was found to be associated with a steep learning curve for less experienced users 3 and thus might have limitations for rapid clinical usage.…”
mentioning
confidence: 99%
“…They reported that the SSMS had excellent correlation with the curve acceleration phase (r = 0.9) in 22 female subjects and excellent reliability among senior orthopaedic surgeons 4 . However, a subsequent validation study of 275 patients demonstrated a steep learning curve for less experienced users 16 . Other recently reported simplified models using the olecranon apophysis 17 or the distal part of the radius and the ulnar epiphysis 3 (DRU classification) were either not evaluated in strictly conducted longitudinal studies or not fully validated through comparison with the standard DSA and RUS scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Radiographically, both the TOCI and the SSMS still rely on distal radial epiphyseal fusion status to determine the end of growth, although it is controversial whether clinically relevant growth is still possible at the late radiographic stages of fusion of the distal radial physis 16 . The SSMS may provide more clarity about growth remaining at this stage since it shows the distal radial physis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are needed to validate this DRU classification in other ethnicities and populations and to further directly compare it with other new and established skeletal maturity schemes. 24 25 26 27 …”
Section: Discussionmentioning
confidence: 99%